Bio‐probing with nonresonant surface‐enhanced hyper‐Raman scattering excited at 1, 550 nm. (16th August 2020) - Heiner, Zsuzsanna; Madzharova, Fani; Živanović, Vesna; Kneipp, Janina
Abstract: The two‐photon excited process of surface‐enhanced hyper‐Raman scattering (SEHRS) provides advantages for studies of complex biological samples, yet suitable SEHRS nanoprobes and labels, as well as experimental conditions, must be established. Here, SEHRS spectra of the four reporter molecules (2‐naphthalenethiol [2‐NAT], para‐ aminothiophenol ( p ATP), para‐ nitrothiophenol ( p NTP), and crystal violet), as well as the two antidepressant drugs (desipramine and imipramine) were obtained at an excitation wavelength of 1, 550 nm using different citrate‐stabilized gold nanoparticles and silver nanoparticles, and under conditions that permit experiments with living cultured cells. As the results suggest, the short‐wave infrared laser excitation and the hyper‐Raman scattered light (corresponding to wavelengths > 775 nm) match the plasmonic properties of the employed gold and silver nanoaggregates, as well as the requirements regarding the viability of the cells. The two‐photon excited spectra of three types of SEHRS labels containing 2‐NAT as reporter inside macrophage cells show that molecules in the cellular environment can also be observed. The possibility to use short‐wave infrared excitation with gold nanostructures has important implications for the utilization of SEHRS in bio‐probing. Abstract : Surface‐enhanced hyper‐Raman scattering (SEHRS) spectra of four reporter molecules and two drugs were obtained at an excitation wavelength of 1, 550 nm using gold and silver nanoparticles under conditions that permit experiments with living cultured cells. Inside the cells, SEHRS signals of both, reporter molecules and intrinsic biomolecules were measured. The results demonstrate applicability of gold and silver SEHRS nanoprobes with short‐wave infrared excitation in complex biological samples and therefore represent a further step towards more biocompatible SEHRS probing.